Cradle-to-gate life cycle assessment of hemp utilization for biocomposite pellet production: A case study with data quality assurance process - Niloofar Akbarian-Saravi; Taraneh Sowlati; Abbas S. Milani (Cleaner Engineering and Technology)
Natural fiber biomass pre-processing practices, including collection and particle size reduction, are crucial for sustainable manufacturing. This industrial case study evaluates the environmental impact of producing fully hemp-derived biocomposite pellets using different biomass collection and pre-processing equipment configurations, in order to identify the most efficient and eco-friendly operational option. The system boundary follows a cradle-to-gate approach, covering upstream activities such as cultivation, harvesting, size reduction, transportation, and pellet manufacturing. Namely, an attributional Life Cycle Assessment (LCA) is performed using a functional unit of 1 tonne of biocomposite, comparing four Supply Chain (SC) design alternatives involving different baler (round/square) and size reduction equipment (full/half screen hammer mill) options. We specifically delve into the relative difference of the combination of a full-screen hammer mill and a square baler (called ''full-square'' as a best-case/reference alternative), as compared to the half-screen hammer mill and round baler (''half-round'' as a worst-case alternative). Results indicated that the half-round alternative exhibited 30–44 % higher environmental impacts due to 30 % higher harvested biomass and 9 % higher diesel usage per tonne of produced biocomposite, but resulted in higher product quality compared to the full-square alternative. The harvesting stage, linked to the use of biomass, fertilizers, and diesel fuels, was identified as a critical contributor to the environmental impact in all the important impact categories. Sensitivity analysis revealed that a 10–30 % increase in biomass yield could reduce impacts across all categories by approximately 7–20 %. Further exploring the potential for environmental impact mitigation, a scenario-based improvement model integrating substitution of nitrogen fertilizer with compost, diesel-to-natural gas switching, ethanol recycling, and increased hemp yield, was conducted and it demonstrated up to 85 % GWP reduction compared to the baseline. Also, the improved biocomposite scenario achieved 57 % lower GWP and 43 % lower smog formation than a virgin PET, while outperforming it in fossil fuel depletion. These findings support the viability of hemp-based biocomposites under improved conditions and emphasize the importance of strategic SC decisions for sustainable material development.